2011
DOI: 10.1016/j.meegid.2011.01.007
|View full text |Cite
|
Sign up to set email alerts
|

An emerging recombinant cluster of nephropathogenic strains of avian infectious bronchitis virus in Korea

Abstract: The infectious bronchitis virus (IBV) is continuously evolving through point mutation and recombination of their genome, subsequently the emergence of IBV variants complicates disease control. The objective of this study was to investigate genetic characterization of new IBV variants isolated from commercial chicken flocks in Korea collected between 2005 and 2010. Phylogenetic analysis revealed that all new IBV isolates belonged to Korean group II (K-II), which included the nephropathogenic IBV strains. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 23 publications
2
63
0
2
Order By: Relevance
“…Some vaccines, such as Mass-type H120 and 4/91-type 4/91 vaccine strains, could not provide effective protection against CK/CH/2010/JT-1 infection. In addition, the CK/ CH/2010/JT-1-like isolates form a new genotypic cluster, which is similar to a new IBV cluster in Korea (Lim et al, 2011).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Some vaccines, such as Mass-type H120 and 4/91-type 4/91 vaccine strains, could not provide effective protection against CK/CH/2010/JT-1 infection. In addition, the CK/ CH/2010/JT-1-like isolates form a new genotypic cluster, which is similar to a new IBV cluster in Korea (Lim et al, 2011).…”
Section: Discussionmentioning
confidence: 74%
“…More and more recombination events have been reported in IBV, and they are distributed throughout the entire genome (Brooks et al, 2004;Kuo et al, 2013;Thor et al, 2011). Recently, a new recombinant cluster of nephropathogenic IBVs able to cause death, respiratory signs and nephritis in infected chickens emerged in Korea (Lim et al, 2011(Lim et al, , 2015. Therefore, studies on the function of recombination in the antigenicity and pathogenicity of IBV are very important, potentially allowing IBV evolution to be predicted and better strategies for IBV control to be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, further studies are necessary to reveal the biological functions of 3a, 3b, and 5b. To date, recombination analyses have only focused on the S1 gene but ours and other comparative genomics studies have revealed multiple recombination sites (S2, 3a, and 3b) in IBV genomes [11,39,40,41]. Therefore, further studies on the recombinations of multiple genes, including S1, S2, 3a, 3b, and 5b may shed light on the evolution of IBV and its pathogenicity under host immunity.…”
Section: Discussionmentioning
confidence: 96%
“…K-IIb (QX-type) strains which might have been introduced to Korea from China were first isolated in 2003 and showed different antigenicity from K-IIa (KM91-type) [7,10]. Recently, new recombinant viruses of KM91-type and QX-type strains, and variant strains showing very low amino acid identity (<58.7%) compared to those of previous isolates have been reported [8,11]. …”
Section: Introductionmentioning
confidence: 99%
“…To analyze the recombination patterns of the PCV2 genome sequences obtained in our study, putative parents were sought using a previously described method (Lim et al, 2011;Cai et al, 2012). Nucleotide identity between the putative recombinant clusters and their putative parents was calculated using the recombination analysis software SimPlot (version 3.5.1) (Lole et al, 1999).…”
Section: Recombination Analysismentioning
confidence: 99%